Association of Insulin and Cholesterol Levels With Peripheral Nervous System Function in Overweight Adults: A 3-Year Follow-up. Issue 6 (November 2017) - Isojärvi, Henri; Keinänen-Kiukaanniemi, Sirkka; Kallio, Mika; Kaikkonen, Kaisu; Jämsä, Timo; Korpelainen, Juha; Korpelainen, Raija
Abstract : Purpose: The purpose of this prospective 3-year follow-up was to investigate the association of glucose, insulin, and cholesterol levels with peripheral nervous system function in overweight and obese subjects. Methods: Forty nondiabetic overweight and obese adults were enrolled, of whom 29 completed the follow-up. Peripheral nervous system function was measured and defined by conduction studies of the peroneal motor nerve and the radial, sural, and medial plantar sensory nerves. Serum insulin and glucose levels were determined with an oral glucose tolerance test, and cholesterol levels were measured. The measurements were performed at baseline and after 3 years. Results: The change in serum insulin level at 120 minutes after an oral glucose tolerance test was positively associated with changes in peroneal nerve conduction velocities and F-wave mean, sural nerve conduction and medial plantar nerve conduction velocities. Action potential amplitudes decreased consistently and significantly in all sensory nerves. Conclusions: The change in serum insulin level at 120 minutes appears to be positively associated with changes in nerve conduction velocities more than 3 years but not with nerve action potential amplitudes. Significant decreases in the action potential amplitudes of all sensory nerves suggest that such changes might be the earliest detectable sign of damage to the peripheral nervous system in overweight and obese people without type 2 diabetes.